Ethnographic Excursions in the Pentecostal Making and Remaking of Men - Thornton, Brendan Jamal (PentecoStudies, 2024)
Following pioneering work on Pentecostalism and women, interest in the study of Pentecostal men and masculinities has grown markedly over the past decade. Research in this area, particularly in places like Africa and Latin America, has helped deepen scholarly appreciation for how gender discourses shape and are shaped by churchgoers in powerfully meaningful and often surprising ways. Yet, despite their ubiquity, issues of masculinity in the church are still frequently overlooked and seldom engaged with critically. Reflecting on my own research on men, masculinity, and Pentecostal conversion in the Dominican Republic, this essay reviews several noteworthy themes and questions in the study of Pentecostal masculinities globally, takes stock of important interventions in the field of Pentecostal studies, and offers several critical remarks on methodology for further consideration. I spotlight ethnography as an essential set of tools that are sensitive to the social dynamics of gender and conversion and uniquely equipped to account for the diverse and often uneven lived experiences of male and female churchgoers.